PSEUDO-DEMOCRACY - Agus Raharjo (Jurnal Dinamika Hukum, 2017)
Simultaneous regional election is a happening legal issue in early 2017. It involves 102 regions which consist of 94 districts/cities and 8 provinces conducting the elections. In the context of autonomy, the sustainability of regional elections is an attempt to seek an aspirative, accommodative and progressive leader profile. Leadership figures which are close to society become the key of success for development and empowerment of the region by its characteristics.....